2014
DOI: 10.1111/1440-1681.12271
|View full text |Cite
|
Sign up to set email alerts
|

Emerging role of cystic fibrosis transmembrane conductance regulator as an epigenetic regulator: linking environmental cues to microRNAs

Abstract: SUMMARYAlthough microRNAs (miRNAs) have been recognized as one of the important epigenetic mechanisms that regulate gene expression in response to changes in the environment, the links between environmental cues and changes in miRNAs remain largely unknown. Localized to the cell membrane and recognized as an anion channel, the cystic fibrosis transmembrane conductance regulator (CFTR) has recently been shown to mediate important signalling pathways leading to activation of miRNAs. This brief review summarizes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 146 publications
(131 reference statements)
1
6
0
Order By: Relevance
“…3 ). Together, these data support the emerging concept of CFTR as epigenetic modulator 39 . Along these lines, it has been recently reported that CFTR regulates miR-125b expression with a bicarbonate-dependent mechanism 40 .…”
Section: Discussionsupporting
confidence: 74%
“…3 ). Together, these data support the emerging concept of CFTR as epigenetic modulator 39 . Along these lines, it has been recently reported that CFTR regulates miR-125b expression with a bicarbonate-dependent mechanism 40 .…”
Section: Discussionsupporting
confidence: 74%
“…The complex relationship between autoinflammation, CFTR, innate immunity and infection is poorly understood, and may be related to macrophage dysfunction, abnormal phagocytic killing of P. aeruginosa , and impaired degranulation of antimicrobial proteins through defective activation of the GTP‐binding protein Rab27a . In addition, CFTR dysfunction results in increased sensitivity to LPS (a major constituent of the outer membrane of Gram‐negative bacteria) stimulation, altered inflammatory signalling caused by abnormal neutrophil extracellular trap formation , and activation of microRNAs (miRNAs) and NF‐κB. These bacteria trigger the NLRP3 inflammasome through cytosolic receptors, resulting in increased caspase‐1 protease and IL‐1β and IL‐18 production (Fig.…”
Section: Autoinflammation and Infectionmentioning
confidence: 99%
“…More interestingly, the CFTR/HCO 3 − /sAC/cAMP pathway was found to regulate miR‐125 in the embryo, through PKA and NFkB activation, which suppresses the p53‐mediated development arrest . This provides the first evidence for the involvement of the CFTR/HCO 3 − /sAC/cAMP signalling in epigenetic regulation . As in the case of sperm capacitation, Cl − is also required for preimplantation development.…”
Section: Cftr/hco3−‐dependent Sac Signallingmentioning
confidence: 80%